Evaluation of critical shoulder angle and acromion index in patients with anterior shoulder instability and rotator cuff tear - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2021)
Objective: The aim of this study was to evaluate glenohumeral morphologic differences and their correlation between glenohumeral instability and rotator cuff pathology. Methods: Two-hundred radiographs and 100 MRI scans of 100 patients in whom the diagnosis of Anterior Shoulder Instability (Anl) or Rotator Cuff Tear (RCT) was arthroscopically verified were retrospectively identified and included in the study. All the patients were categorized into two groups: 50 patients with Anl (23 female, 28 male; mean age = 29 +/- 7.4) and 50 patients with RCT (28 female, 22 male). Two separate control groups were then formed, one of which included contralateral shoulders of patients in the AnI group, and the other consisted of contralateral shoulders of patients in the RCT group. The x-ray and MRI scans were examined by an orthopedic surgeon and a radiologist. The Acromial Index (AI) and the Critical Shoulder Angle (CSA) were measured on true anteroposterior shoulder radiographs; Glenoid Inclination (GI), Glenoid Version (GV), and Acromion Angulation (AA) were measured on MRI. Results: In the AnI group, the measurements were as followed: AI, 0.66 +/- 0.03; CSA, 33 degrees +/- 2.85; GI, 3.4 degrees +/- 6.2; GV, 4.1 +/- 4.3; and AA, 12.9 +/- 8.3. In the RCT group, AI 0.71 +/- 0.04; CSA, 36 degrees +/- 2.69; GI, 9.1 +/- 5; GV, 6.7 degrees +/- 5.7; and AA, 14.3 degrees +/- 8.7. A moderate correlation was found between CSA and GI (r = 0.41, P = 0.001) and between AI and GI (r = 0.42, P = 0.014). A weak correlation was found between AI and GI in the AnI group (r = 0.22, P = 0.001). The inter- and intra-observer intraclass correlation coefficients were respectively 0.81 and 0.84 for AI, 0.88 and 0.92 for CSA, 0.72 and 0.76 for GI, 0.69 and 0.73 for GV, and 0.72 and 0.77 for AA. Conclusion: The results of this study have shown that lower AI, GI, and antevert GV may be associated with AnI. Investigating CSA, AI, and GV could be useful for diagnostic evaluation of patients with AnI.
Keywords: Critical shoulder angle; Acromion index; Glenoid inclination; Glenoid version; Rotator cuff tear; Anterior instability; Shoulder radiographs; Morphology; X-ray; GLENOID INCLINATION; GLENOHUMERAL JOINT; BONE LOSS; ASSOCIATION; CLASSIFICATIONS; OSTEOARTHRITIS; VERSION; AGE